Potential of Using Limestone Rocks Accumulated in Al-Samawa Stone Quarry, South Iraq, for The Stationary Phase in A Column Chromatography Separation - AbdulHussein, Maitham AbdulRedha (Iraqi Journal of Science, 2023)
This investigation aims to determine whether it is feasible to use the limestone rocks found in the Al-Samawa stone quarry in southern Iraq as the stationary phase in column chromatography separation. Together with the chromatographic application, the physical and chemical characteristics of the rocks are examined. SiO2, SO4, PO4, NO3, and Cl are the negative ions, while Ca, Mg, Na, K, and Li are the positive ions. The limestone samples are characterized via chromatographic analysis. The results suggest that limestone samples could be used as an adsorbent material for chromatographic separation techniques. Additionally, samples from the Nasiriyah refinery's crude oil can be used to separate oil.